Recursos hídricos da bacia hidrográfica da Estrada Nova, Belém - Pará: elementos para gestão - RODRIGUES, Érika do Socorro Ferreira (2019)
With an area of 3 566.079 km ² and a population of 2,176,334 inhabitants (IBGE, 2013), the Metropolitan Region of Belem (RMB) has an area that is influenced by 14 watershed with strong urban among them is the watershed Estrada Nova (BHEN) which consists of 8 districts of Belém. The area in the process of use and occupation of land occurred in a disorderly manner, directly reflected in patterns of occupation observed in the vicinity of streams responsible for the drainage watershed: buildings low-income families too close to the watercourse. In 2007 the districts of the Watershed Estrada Nova (BHEN) were directly linked to the project of Social and Environmental Recovery of the watershed Estrada Nova - . PROMABEN, home to nearly a quarter of the population of the capital. The overall objective of this study aims to provide a set of basic elements requirements for the integrated management of water resources, thus contributing to better use of the physical environment, municipal and state planning, understand the relationship between surface water and groundwater within the watershed and develop a proposed alternative water supply for BHEN population, Belem- PA.